Evaluation of Long-Term and High-Resolution Gridded Precipitation and Temperature Products in the Qilian Mountains, Qinghai–Tibet Plateau - Li, Yanzhao; Qin, Xiang; Liu, Yushuo; Jin, Zizhen; Liu, Jun; Wang, Lihui; Chen, Jizu (Frontiers in Environmental Science, 2022)
Long-term and high-resolution gridded products of precipitation and temperature data are highly important to study the changes of climate and environment under global warming. Considering uncertainties of these products in mountainous areas, it is necessary to evaluate the data reliability. This study evaluates the performances of CMFD (i.e. China Meteorological Forcing Dataset) and ERA5-Land in simulating precipitation and temperature in Qilian Mountains over the period of 1980-2018. We use the observation data of 28 basic meteorological stations in the Qilian Mountains to compare with the reanalysis products. Error metrics (i.e. the correlation coefficient (CC), the root mean square error (RMSE), the mean absolute error (MAE), and the relative bias (BIAS)) are used to quantify the monthly differences in existence between the observed data and reanalysis data. Our findings indicate that both CMFD and ERA5-Land could well reproduce the spatial distribution of mean monthly precipitation and temperature in the region. Good correlation is found between CMFD and OBS under different amount of monthly precipitation conditions. The monthly average temperatures of CMFD and ERA5-Land reveal high correlation with the observed results. Moreover, the CC values of CMFD and ERA5-Land precipitation products show the highest in autumn and the lowest in winter, and the CC values of both CMFD and ERA5-Land temperature products are higher in spring and autumn. However, we find that, both reanalysis products underestimate the temperature to varying degrees, and the amount of precipitation is overestimated by ERA5-Land. The results of evaluation show that the errors in precipitation yielded by CMFD as a whole are distinctly fewer than those yielded by ERA5-Land, while the errors in air temperature yielded by both ERA5-Land and CMFD are nearly identical to each other. Overall, ERA5-Land is more suitable for studying the trends on temperature changes in the Qilian Mountains than that of CMFD. As for simulation of precipitation, CMFD performs better in the central and eastern parts of the Qilian Mountains, whereas ERA5-Land does better in the western part of the Qilian Mountains.